PERAN PARIWISATA DAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENGURANGI KEMISKINAN DI PROVINSI JAWA TENGAH - Dyah Makutaning Dewi; Istu Indah Setyaningsih; Ika Yuni Wulansari (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2023)
Central Java is one of Indonesia's provinces with the second-largest number of poor people in 2018. However, in 2020 the Central Java Provincial Government became a champion in reducing poverty. In addition, the province also achieved various achievements in the tourism sector in 2019. The decline in the number of poor people is inseparable from many factors, such as the tourism sector and the development of Technology, Information, and Communication (ICT). This research aims to provide an overview of the condition of the number of poor people, the tourism sector, and the ICT sector in Central Java Province as well as to analyze the influence of the tourism sector and ICT on the number of poor people in Central Java Province. This study uses panel data sourced from the Central Statistics Agency and the Youth, Sports, and Tourism Office (Disporapar) of Central Java. Results showed that the percentage of mobile phone owners, internet users, and tourist destinations negatively and significantly affected the number of poor people in Central Java Province. Therefore, the decline in the number of poor people can be supported through the tourism sector and the role of technology.